Diretrizes cartográficas para mapas turísticos visando um destino turístico inteligente, aplicado ao Jardim das Esculturas no município de Júlio de Castilhos, RS - Silva, Marinêz da (2023)
Tourism has been a great expansion activity. The development of studies and analysis on the ways and possibilities of better serving the tourist are important actions that can contribute significantly to the development of these destinations, as well as provide products that enable a better experience and satisfaction to the tourist. The main objective of this research was to systematize the parameters that contribute to a better orientation of tourist maps from the perspective of the tourist and the pillars of innovation and technology of a smart tourist destination. It contributes to the literature on the tourist experience from the user's point of view. Qualitative research was conducted in a tourist destination called Jardim das Esculturas, located in the city of Júlio de Castilhos/RS, where 106 visitors answered a questionnaire composed of open and closed questions. The answers were systematized in an electronic spreadsheet, in order to treat and analyze the data collected, which served as a subsidy for the development of tourist maps. The results demonstrated that the most prevalent needs of the tourist are o know the route of the tourist destination and guide himself inside it. For this purpose, a static map was created with the location of the niches and a web map with the possible access routes to the tourist destination. This research has an important contribution through the new cartography and geoinformatics, as they play a significant role in the development of tourism, by making possible a tourist map centered on the user after analyzing their needs, enriching the tourist experience.